THE EFFECT OF WORK LIFE BALANCE, LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE - Arfandi; Muhammad Kasran (Universitas Dr. Soetomo, 2023)
This study aims to determine the effect of WLB, leadership style, organizational culture on employee performance at PT. SGS Luwu, South Sulawesi Province. The approach in this study used a survey method, with a total of 200 employees as respondents. Sampling in this study was carried out randomly. The hypothesis was tested using the structural equation modeling (SEM) data analysis method with the help of software, namely Analysis Moment of Structure (AMOS) 26. The results of this study explain that: 1). Work life balance has significant influence on organizational culture. This means that WLB will increase along with the organizational culture that is implemented in employee behavior. 2). Leadership style has a positive and significant effect on organizational culture. This means that the higher the level of leadership style, the organizational culture will also increase. 3). Work life balance has a positive and significant effect on employee performance. This means that the better WLB, the happier employees will be and will make employees more productive in providing better performance to the company. 4) Leadership style has an influence and is significant on employee performance. This means that leadership style has an effect on improving employee performance. 5). Organizational culture has a positive and significant effect on employee performance. This means that the higher the level of organizational culture, the higher the employee performance.